Automated Fabric Feeding Guide in Continuous Rotary Fabric Printing Machine - Madhan, Mohan M; Baluprithiviraj; Elakhiya, K.B; Kabilan, K; Balaji, Prasanth.S; Janarthanan, S (2023 2nd International Conference on Applied Artificial Intelligence and Computing (ICAAIC), 2023)
Despite the millions of dollars invested in research, the industry is still a long way from developing a completely autonomous process for initial cloth feeding technique for creating new designs via auto textile machines. The misaligned initial fabric feed lead to complete collapse in design of a multi-colour printing sequence process. Therefore, an attempt is made to ensure the initial feeding issues in first design of the batch process in the rotary printing machine through Infra-Red control pneumatic systems. Hence a control arrangement is made so as to ensure and maintain the equal fabric feed using Infra-Red sensed Pneumatic control system before printing process starts. The signal from Infra-Red Sensor arrangement fixed at the edges of the fabric used to detect the right position of the fabric and pneumatic system actuated by accelerometer to maintain the fabric in a straight line. The feed roller is tilted slightly to rearrange the feed angle through the pneumatic control.